FROM MOBILE BANKING TO SUPER‑APPS: INTEGRATING PAYMENTS, TRADING, AND WEALTH MANAGEMENT - Hrachya Papikyan (American Journals Publishing, 2025)
Background: In the past ten years, leading mobile banking apps have grown far beyond basic deposits and payments. They offer services such as stock trading, robo‑advisory, and packaged investment products by changing into “super‑apps.” This makes banking easier for users and opens new opportunities for providers, but it’s noteworthy to mention that, it also raises concerns about market power, consumer protection and regulation bis.orgbis.org. Payment improvement (wallet penetration, APIs, instant/fast payment rails,) has made it easier for companies and different financial services to connect. Open-banking and open-finance frameworks have expanded to allow data sharing across not just payment accounts, but also investments, saving and pensions finance.ec.europa.eufinance.ec.europa.eu. At the same time, conduct rules like the UK’s Consumer Duty are making financial institutions prioritize visible benefits for customers and ensure the responsible promotion of investment products within multi-functional digital platforms. Commercially, bundling creates cross‑sell flywheels (payments → investing/savings → credit/insurance) and diversified fee streams, while technically it demands microservices, consolidated identity/KYC, and product‑specific safekeeping and disclosures (e.g., deposit insurance vs SIPC). Last research on “big techs in finance” suggests scale economies in data and distribution can lower access costs meanwhile it makes market power more concentrated and complicate oversight bis.orgbis.org.Objective: To explore how digital banks integrate payments, trading, and management; identify top technical, licensing, and business model trends; and capture policy and managerial implications.